(untitled) (Revista Archai, 2023)
In the present work, I will review how Aristotle understood the connection between reason and emotion - particularly, angry actions - in order to demonstrate that it is due to the presence of intellectual factors that emotions become ethically relevant and not merely an uncontrolled reaction. Then, I will summarize Aristotle’s repeated analogies between reason as the master and anger as the slave to explain their connection. My specific contribution to the topic will be to reverse this analogy and, instead of using it as an example of the lógos-thymós connection, make the latter an example of the despótes-doûlos connection as described in Politics I. If my hypothesis is plausible, establishing the actions and virtues of a slave will help shed light on the type of morality inherent in angry actions.